Implementasi Nilai-Nilai Toleransi dalam Pembelajaran PAI - Tristan Malik Alfikri; Ahmad Kosasih (An-Nuha, 2022)
The lack of affective emphasis in learning Islamic Religious Education is one of the causes of the emergence of issues of intolerance that are very influential for society. This study aims to determine how the implementation of tolerance values ​​in Islamic religious education learning, especially in SDN 38 Lubuk Buaya Padang. This study uses a qualitative method with a case study approach (case study design). The research data was obtained through observation, documentation, and interviews with selected sources using purposive sampling technique, all informants were active school residents. All research results were then analyzed using the Miles and Huberman model analysis techniques, namely data reduction, data presentation, and drawing conclusions. The results showed that the forms of implementing tolerance values ​​in Islamic Religious Education learning at SDN 38 Lubuk Buaya Padang were: 1) Learning in an atmosphere of difference 2) Allowing students to pray according to their respective beliefs, 3) Allowing non-Muslim students follow the Islamic Education learning process, 4) Provide equal treatment for students regardless of background, 5) Tolerate uniform rules for non-Muslim students 6) Help each other. The results of this study can be used as initial data for future researchers in examining this problem in different contexts and issues.